Evaluation of multiple water quality indices for irrigation purposes for the Bheri and Babai River systems, Nepal - Khatri, Kumar; Jha, Bibhuti Ranjan; Khadka, Udhab Raj; Gurung, Smriti (Nepal Journal of Environmental Science, 2022)
The main purpose of this study was to assess the irrigation water quality of the Bheri and Babai Rivers and their tributaries prior to the proposed inter-basin water transfer (IBWT) in western Nepal. A total of 40 water samples from five sites in each river system were collected from January (winter), March-April (spring), June (summer) and October (autumn) in 2018; and some important irrigation water quality parameters were assessed. All the assessed parameters viz. pH, Total Dissolved Solids (TDS), Total Hardness (TH), permeability index (PI), percent sodium (%Na), sodium adsorption ratio (SAR), magnesium hazard (MAR), residual sodium carbonate (RSC), Kelly’s index (KI) from all sites were observed suitable for irrigation. USSL diagram showed that water from both the rivers belongs to the S1-C2 category indicating good for irrigation purposes. The Wilcox diagram revealed that all samples fall into the excellent to a good class. Based on Irrigation Water Quality Index (IWQI), 3 sampling sites fall in the high restriction category and 7 sampling sites fall in the moderate restriction category, indicating anthropogenic impacts on irrigation water quality at some sites.